High‐resolution ultrasound demonstrates in vivo effects of wrist movement on the median nerve along the forearm. Issue 5 (1st September 2021) - Jengojan, Suren; Schellen, Christoph; Dovjak, Gregor; Schmidhammer, Robert; Weber, Michael; Kasprian, Gregor; Bodner, Gerd
Abstract: Introduction/Aims: High‐resolution ultrasound (HRUS) is the imaging method of choice to visualize peripheral nerve size, structure, and biomechanical performance. The purpose of this study was to show and quantify the effects of active and passive wrist alignment on median nerve (MN) cross‐sectional area (CSA) along the forearm in a healthy population. Methods: Sixteen healthy volunteers underwent HRUS of their dominant forearm ( n = 16, 10 males, 6 females, 18–55 y of age). Median nerveʼs CSA was assessed at four defined areas on the forearm in relation to active and passive wrist alignment. Results: Changes in wrist alignment were significantly associated with MN CSA ( P < .001), regardless if the wrist was moved actively or passively. MN CSA was lowest during passive extension of the wrist joint and highest during passive flexion of the wrist joint (range: 4.5–23.2 mm 2 ). Discussion: The elasticity of nerve tissue, the loose connective tissue between the fascicles, and the paraneurium allow peripheral nerves to adapt to longitudinal strain. HRUS enables the demonstration of significant median nerve CSA changes along the forearm during active and passive wrist movement in healthy volunteers.